2005
DOI: 10.1681/asn.2005010054
|View full text |Cite
|
Sign up to set email alerts
|

Protection against Renal Ischemia Reperfusion Injury by CD44 Disruption

Abstract: Inflammation contributes to renal ischemia reperfusion (I/R) injury, potentially causing renal dysfunction. The inflammatory infiltrate mainly consists of neutrophils, which are deleterious for the renal tissue. Because CD44 is expressed by neutrophils and is rapidly upregulated by capillary endothelial cells after I/R injury, it was hypothesized that CD44 might play an important role in the development of I/R injury. This study showed that rapid CD44 upregulation on renal capillary endothelial cells mediates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
100
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 44 publications
10
100
0
1
Order By: Relevance
“…[8][9][10]24,25 In light of the important role of neutrophils and macrophages in host defense in pneumococcal pneumonia, 3 we determined the cellular composition of BALF harvested at 6, 24 or 48 h after infection with a lethal dose of S. pneumoniae (10 4 CFU). Whereas, macrophage numbers were similar in BALF harvested from CD44 KO and WT mice at all time points (data not shown), neutrophil counts were slightly enhanced at 6 h and more clearly at 24 h after infection, although these differences did not reach statistical significance (P ¼ 0.16 and P ¼ 0.06, respectively; Figure 3a).…”
Section: Cd44 Deficiency Results In Enhanced Early Neutrophilmentioning
confidence: 99%
See 2 more Smart Citations
“…[8][9][10]24,25 In light of the important role of neutrophils and macrophages in host defense in pneumococcal pneumonia, 3 we determined the cellular composition of BALF harvested at 6, 24 or 48 h after infection with a lethal dose of S. pneumoniae (10 4 CFU). Whereas, macrophage numbers were similar in BALF harvested from CD44 KO and WT mice at all time points (data not shown), neutrophil counts were slightly enhanced at 6 h and more clearly at 24 h after infection, although these differences did not reach statistical significance (P ¼ 0.16 and P ¼ 0.06, respectively; Figure 3a).…”
Section: Cd44 Deficiency Results In Enhanced Early Neutrophilmentioning
confidence: 99%
“…Several studies have shown a positive role of CD44 in inflammatory cell recruitment, 10,25,[36][37][38][39][40][41] whereas other investigations reported enhanced inflammatory cell migration in the absence of CD44. 8,9,24,35 This discrepancy is probably because of the differences in the cell type studied, the stimulus and organ involved, and the severity of the insult.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Renal I/R injury was induced as described previously [15][16][17] . Briefly, both renal arteries were clamped for 30 min under general anesthesia (0.07 ml/10 g mouse of fentanyl citrate fluanisone midazolam mixture containing: 1.25 mg/ml midazolam (Roche Diagnostics Corp.), 0.08 mg/ml fentanyl citrate, and 2.5 mg/ml fluanisone (Janssen Pharmaceutica)), which induces profound renal damage and dysfunction without inducing mortality [17] .…”
Section: Renal I/r Injury Modelmentioning
confidence: 99%
“…Renal function and tubular damage was determined as described previously [15,16] . The degree of tubular damage was assessed on periodic acid-Schiff diastase (PASD)-stained paraffinembedded tissue sections.…”
Section: Plasma Biochemical Analysis Histology and Immunohistochemistrymentioning
confidence: 99%